2D Carbon Allotrope with Incorporated Au-Ag Nanoclusters - Laser-Induced Synthesis and Optical Characterization - Manshina, Alina; Petrov, Yuriy; Kolesnikov, I.; Mitetelo, N. V.; Murzina, T. V.; Butt, M. A.; Neugebauer, M.; Banzer, Peter; Leuchs, Gerd (2018 Conference on Lasers and Electro-Optics Pacific Rim, CLEO-PR 2018, 2019)
We discuss the laser-induced fabrication and detailed structural and optical characterization of a novel carbon allotrope intercalated with bimetallic nanoclusters.
CRIS-Team Scopus Importer:2019-05-21

Chiral optical response of planar and symmetric nanotrimers enabled by heteromaterial selection - Banzer, Peter; Wozniak, Pawel; Mick, Uwe; De Leon, Israel; Boyd, Robert W. (Nature Communications, 2016)
Chirality is an intriguing property of certain molecules, materials or artificial nanostructures, which allows them to interact with the spin angular momentum of the impinging light field. Due to their chiral geometry, they can distinguish between left-and right-hand circular polarization states or convert them into each other. Here we introduce an approach towards optical chirality, which is observed in individual two-dimensional and geometrically mirror-symmetric nanostructures. In this scheme, the chiral optical response is induced by the chosen heterogeneous material composition of a particle assembly and the corresponding resonance behaviour of the constituents it is built from, which breaks the symmetry of the system. As a proof of principle, we investigate such a structure composed of individual silicon and gold nanoparticles both experimentally, as well as numerically. Our proposed concept constitutes an approach for designing two-dimensional chiral media tailored at the nanoscale, allowing for high tunability of their optical response.

Classically entangled optical beams for high-speed kinematic sensing - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, Marco; Giacobino, Elisabeth; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optica, 2015)
Tracking the kinematics of fast-moving objects is an important diagnostic tool for science and engineering. Here, we demonstrate an approach to positional and directional sensing based on the concept of classical entanglement in vector beams of light [Found. Phys. 28, 361–374 (1998)]. The measurement principle relies on the intrinsic correlations existing in such beams between transverse spatial modes and polarization. The latter can be determined from intensity measurements with only a few fast photodiodes, greatly outperforming the bandwidth of current CCD/CMOS devices. In this way, our setup enables two-dimensional real-time sensing with temporal resolution in the GHz range. We expect the concept to open up new directions in metrology and sensing.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Classical and quantum physics; Optical sensing and sensors

Demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Optics InfoBase Conference Papers, 2013)
We demonstrate and discuss a state of light with purely transverse angular momentum - a photonic wheel - generated by tight focusing of polarization tailored light. We use an experimental nanoprobing technique to measure the corresponding distribution.
CRIS-Team Scopus Importer:2022-06-05

Emission of circularly polarized light by a linear dipole - Neugebauer, Martin; Banzer, Peter; Nechayev, Sergey (Science Advances, 2019)
Controlling the polarization state and the propagation direction of photons is a fundamental prerequisite for many nanophotonic devices and a precursor for future on-chip communication, where the emission properties of individual emitters are particularly relevant. Here, we report on the emission of partially circularly polarized photons by a linear dipole. The underlying effect is linked to the near-field part of the angular spectrum of the dipole, and it occurs in any type of linear dipole emitter, ranging from atoms and quantum dots to molecules and dipole-like antennas. We experimentally observe it by near-field to far-field transformation at a planar dielectric interface and numerically demonstrate the utility of this phenomenon by coupling the circularly polarized light to the individual paths of crossing waveguides.
CRIS-Team Scopus Importer:2019-07-09

Enhanced spin-orbit coupling in an epsilon-near-zero material - Eismann, Jörg; Ackermann, Lisa; Kantor, Brian; Nechayev, Sergey; Alam, M. Zahirul; Fickler, Robert; Boyd, Robert W.; Banzer, Peter (Optica, 2022)
Light can carry both spin and orbital angular momentum. While it is known that a nonparaxial circularly polarized beam couples the spin angular momentum to orbital angular momentum, this phenomenon does not hold upon col-limation of the field. With the rising interest in epsilon-near-zero photonics, integral ingredients to this field are the beam-shaping capabilities of such a regime. In this work, it is experimentally shown that a permanent conversion of spin-to-orbital angular momentum arises naturally from an incident circularly polarized field on an isotropic inter-face due to the asymmetry in the Fresnel coefficients. More significantly, the conversion efficiency can be substantially enhanced in the presence of an epsilon-near-zero film due to the unique Fresnel properties exhibited in such a regime. It is further shown that the conversion efficiency scales with the nonparaxiality of the incident field. Our study showcases the intriguing phenomena resulting from the combination of concepts as old as Fresnel coefficients and modern mate-rials such as epsilon-near-zero films. (C) 2022 Optica Publishing Group under the terms of the Optica Open Access Publishing Agreement
CRIS-Team WoS Importer:2022-10-21

Erratum: Lattice-plasmon-induced asymmetric transmission in two-dimensional chiral arrays (APL Photonics (2022) 7 (016105) DOI: 10.1063/5.0074849) - Apurv Chaitanya, N.; Butt, M. A. T.; Reshef, O.; Boyd, Robert W.; Banzer, Peter; De Leon, Israel (APL Photonics, 2022)
The original article1 contains an error in Eq. (1). The correct equation is. (Formula Presented) The original article’s analysis, findings, and conclusions remain the same.
CRIS-Team Scopus Importer:2022-10-14

Exotic looped trajectories of photons in three-slit interference - Magaña-Loaiza, Omar S; De Leon, Israel; Mirhosseini, Mohammad; Fickler, Robert; Safari, Akbar; Mick, Uwe; McIntryre, Brian; Banzer, Peter; Rodenburg, Brandon; Leuchs, Gerd; Boyd, Robert W. (Nature Communications, 2016)
The validity of the superposition principle and of Born's rule are well-accepted tenants of quantum mechanics. Surprisingly, it has been predicted that the intensity pattern formed in a three-slit experiment is seemingly in contradiction with the most conventional form of the superposition principle when exotic looped trajectories are taken into account. However, the probability of observing such paths is typically very small, thus rendering them extremely difficult to measure. Here we confirm the validity of Born's rule and present the first experimental observation of exotic trajectories as additional paths for the light by directly measuring their contribution to the formation of optical interference fringes. We accomplish this by enhancing the electromagnetic near-fields in the vicinity of the slits through the excitation of surface plasmons. This process increases the probability of occurrence of these exotic trajectories, demonstrating that they are related to the near-field component of the photon's wavefunction.

Experimental cross-polarization detection of coupling far-field light to highly confined plasmonic gap modes via nanoantennas - Wen, J.; Banzer, Peter; Kriesch, Arian; Ploss, Daniel; Schmauß, Bernhard; Peschel, Ulf (Applied Physics Letters, 2011)
We experimentally demonstrate the coupling of far-field light to highly confined plasmonic gap modes via connected nanoantennas. The excitation of plasmonic gap modes is shown to depend on the polarization, position, and wavelength of the incident beam. Far-field measurements performed in crossed polarization allow for the detection of extremely weak signals re-emitted from gap waveguides and can increase the signal-to-noise ratio dramatically.
lhft_intern.bib::Wen11

Experimental demonstration of linear and spinning Janus dipoles for polarisation- and wavelength-selective near-field coupling - Picardi, Michela F.; Neugebauer, Martin; Eismann, Joerg S.; Leuchs, Gerd; Banzer, Peter; Rodriguez-Fortuno, Francisco J.; Zayats, Anatoly V. (Light: Science & Applications, 2019)
The electromagnetic field scattered by nano-objects contains a broad range of wavevectors and can be efficiently coupled to waveguided modes. The dominant contribution to scattering from subwavelength dielectric and plasmonic nanoparticles is determined by electric and magnetic dipolar responses. Here, we experimentally demonstrate spectral and phase selective excitation of Janus dipoles, sources with electric and magnetic dipoles oscillating out of phase, in order to control near-field interference and directional coupling to waveguides. We show that by controlling the polarisation state of the dipolar excitations and the excitation wavelength to adjust their relative contributions, directionality and coupling strength can be fully tuned. Furthermore, we introduce a novel spinning Janus dipole featuring cylindrical symmetry in the near and far field, which results in either omnidirectional coupling or noncoupling. Controlling the propagation of guided light waves via fast and robust near-field interference between polarisation components of a source is required in many applications in nanophotonics and quantum optics.
CRIS-Team Scopus Importer:2019-06-21

Experimental demonstration of the geometric spin hall effect of light in highly focused vector beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Lindlein, Norbert; Aiello, Andrea; Marquardt, Christoph; Korger, Jan; Leuchs, Gerd (Quantum Electronics and Laser Science Conference, QELS 2012, 2012)
We demonstrate the geometric spin Hall effect of light by focusing a specially polarization tailored beam of light, resulting in the generation of purely transverse angular momentum in the focal plane. © 2012 OS

Extraordinary transmission through a single coaxial aperture in a thin metal film - Banzer, Peter; Kindler, Jochen; Quabis, Susanne; Peschel, Ulf; Leuchs, Gerd (Optics Express, 2010)
We investigate experimentally the transmission properties of single sub-wavelength coaxial apertures in thin metal films (t = 110 nm). Enhanced transmission through a single sub-wavelength coaxial aperture illuminated with a strongly focused radially polarized light beam is reported. In our experiments we achieved up to four times enhanced transmission through a single coaxial aperture as compared to a (hollow) circular aperture with the same outer diameter.We attribute this enhancement of transmission to the excitation of a TEM-mode for illumination with radially polarized light inside the single coaxial aperture. A strong polarization contrast is observed between the transmission for radially and azimuthally polarized illumination. Furthermore, the observed transmission through a single coaxial aperture can be strongly reduced if surface plasmons are excited. The experimental results are in good agreement with finite difference time domain (FDTD) simulations.
EAM Import::2019-03-14

Free-space propagation of high-dimensional structured optical fields in an urban environment - Lavery, Martin P. J.; Peuntinger, Christian; Günthner, Kevin; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Science Advances, 2017)
Spatially structured optical fields have been used to enhance the functionality of a wide variety of systems that use light for sensing or information transfer. As higher-dimensional modes become a solution of choice in optical systems, it is important to develop channel models that suitably predict the effect of atmospheric turbulence on these modes. We investigate the propagation of a set of orthogonal spatial modes across a free-space channel between two buildings separated by 1.6 km. Given the circular geometry of a common optical lens, the orthogonal mode set we choose to implement is that described by the Laguerre-Gaussian (LG) field equations. Our study focuses on the preservation of phase purity, which is vital for spatial multiplexing and any system requiring full quantum-state tomography. We present experimental data for the modal degradation in a real urban environment and draw a comparison to recognized theoretical predictions of the link. Our findings indicate that adaptations to channel models are required to simulate the effects of atmospheric turbulence placed on high-dimensional structured modes that propagate over a long distance. Our study indicates that with mitigation of vortex splitting, potentially through precorrection techniques, one could overcome the challenges in a real point-to-point free-space channel in an urban environment.
CRIS-Team Scopus Importer:2022-06-05

Generation and subwavelength focusing of longitudinal magnetic fields in a metallized fiber tip - Ploss, Daniel; Kriesch, Arian; Pfeifer, Hannes; Banzer, Peter; Peschel, Ulf (Optics Express, 2014)
We demonstrate experimentally and numerically that in fiber tips as they are used in NSOMs azimuthally polarized electrical fields (|Eazi|2 / |Etot|2 ≈55% ± 5% for extgreekl0= 1550 nm), respectively subwavelength confined (FWHM ≈450 nm ≈ extgreekl0/3.5) magnetic fields, are generated for a certain tip aperture diameter (d = 1.4 extgreekmm). We attribute the generation of this field distribution in metal-coated fiber tips to symmetry breaking in the bend and subsequent plasmonic mode filtering in the truncated conical taper.
EAM Import::2019-03-13

Geometric spin Hall effect of light in tightly focused polarization-tailored light beams - Neugebauer, Martin; Banzer, Peter; Bauer, Thomas; Orlovas, Sergejus; Lindlein, Norbert; Aiello, Andrea; Leuchs, Gerd (Physical Review A - Atomic, Molecular, and Optical Physics, 2014)

GHz kinematic sensing with classically entangled beams of light - Berg-Johansen, Stefan; Töppel, Falk; Stiller, Birgit; Banzer, Peter; Ornigotti, M.; Giacobino, E.; Leuchs, Gerd; Aiello, Andrea; Marquardt, Christoph (Optics InfoBase Conference Papers, 2015)
CRIS-Team Scopus Importer:2021-06-29

Huygens' dipole for polarization-controlled nanoscale light routing - Nechayev, Sergey; Eismann, Jörg; Neugebauer, Martin; Wozniak, Pawel; Bag, Ankan; Leuchs, Gerd; Banzer, Peter (Physical Review A, 2019)
Structured illumination allows for satisfying the first Kerker condition of in-phase perpendicular electric and magnetic dipole moments in any isotropic scatterer that supports electric and magnetic dipole resonances. The induced Huygens' dipole may be utilized for unidirectional coupling to waveguide modes that propagate transverse to the excitation beam. We study two configurations of a Huygens' dipole, longitudinal electric and transverse magnetic dipole moments or vice versa. We experimentally show that only the radially polarized emission of the first and azimuthally polarized emission of the second configuration are directional in the far field. This polarization selectivity implies that directional excitation of either transverse magnetic (TM) or transverse electric (TE) waveguide modes is possible. Applying this concept to a single dielectric nanoantenna excited with structured light, we are able to experimentally achieve scattering directivities of around 23 and 18 dB in TM and TE modes, respectively. This strong directivity paves the way for tunable polarization-controlled nanoscale light routing and applications in optical metrology, localization microscopy, and on-chip optical devices.
CRIS-Team WoS Importer:2019-04-30

Hybrid Orthorhombic Carbon Flakes Intercalated with Bimetallic Au-Ag Nanoclusters: Influence of Synthesis Parameters on Optical Properties - Butt, Muhammad Abdullah; Mamonova, Daria; Petrov, Yuri; Proklova, Alexandra; Kritchenkov, Ilya; Manshina, Alina; Banzer, Peter; Leuchs, Gerd (Nanomaterials, 2020)
Until recently, planar carbonaceous structures such as graphene did not show any birefringence under normal incidence. In contrast, a recently reported novel orthorhombic carbonaceous structure with metal nanoparticle inclusions does show intrinsic birefringence, outperforming other natural orthorhombic crystalline materials. These flake-like structures self-assemble during a laser-induced growth process. In this article, we explore the potential of this novel material and the design freedom during production. We study in particular the dependence of the optical and geometrical properties of these hybrid carbon-metal flakes on the fabrication parameters. The influence of the laser irradiation time, concentration of the supramolecular complex in the solution, and an external electric field applied during the growth process are investigated. In all cases, the self-assembled metamaterial exhibits a strong linear birefringence in the visible spectral range, while the wavelength-dependent attenuation was found to hinge on the concentration of the supramolecular complex in the solution. By varying the fabrication parameters one can steer the shape and size of the flakes. This study provides a route towards fabrication of novel hybrid carbon-metal flakes with tailored optical and geometrical properties.
CRIS-Team WoS Importer:2020-08-14

Interaction of highly focused vector beams with a metal knife-edge - Marchenko, P.; Orlov, S.; Huber, C.; Banzer, Peter; Quabis, Susanne; Peschel, Ulf; Leuchs, Gerd (Optics Express, 2011)
We investigate the interaction of highly focused linearly polarized optical beams with a metal knife-edge both theoretically and experimentally. A high numerical aperture objective focusses beams of various wavelengths onto samples of different sub-wavelength thicknesses made of several opaque and pure materials. The standard evaluation of the experimental data shows material and sample dependent spatial shifts of the reconstructed intensity distribution, where the orientation of the electric field with respect to the edge plays an important role. A deeper understanding of the interaction between the knife-edge and the incoming highly focused beam is gained in our theoretical model by considering eigenmodes of the metal-insulator-metal structure. We achieve good qualitative agreement of our numerical simulations with the experimental findings.
EAM Import::2019-03-13

Interaction of light carrying orbital angular momentum with a chiral dipolar scatterer - Wozniak, Pawel; De Leon, Israel; Hoeflich, Katja; Leuchs, Gerd; Banzer, Peter (Optica, 2019)
The capability to distinguish the handedness of circularly polarized light is a well-known intrinsic property of a chiral nanostructure. It is a long-standing controversial debate, however, whether a chiral object can also sense the vorticity, or the orbital angular momentum (OAM), of a light field. Since OAM is a spatial property, it seems rather counter-intuitive that a point-like chiral object could be able to distinguish the sense of the wave-front of light carrying OAM. Here, we show that a dipolar chiral nanostructure is indeed capable of distinguishing the sign of the phase vortex of the incoming light beam. To this end, we take advantage of the conversion of the sign of OAM, carried by a linearly polarized Laguerre-Gaussian beam, into the sign of optical chirality upon tight focusing. Our study provides for a deeper insight into the discussion of chiral light-matter interactions and the respective role of OAM. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-09-13

Investigating plasmonic gap modes coupled to nanoantennas - Wen, J.; Kriesch, Arian; Ploss, Daniel; Banzer, Peter; Schmauß, Bernhard; Peschel, Ulf (Lasers and Electro-Optics Europe (CLEO EUROPE/EQEC), 2011 Conference on and 12th European Quantum Electronics Conference, 2011)
lhft_intern.bib::Wen2011

Investigating the Optical Properties of a Laser Induced 3D Self-Assembled Carbon–Metal Hybrid Structure - Butt, Muhammad Abdullah; Lesina, Antonino Calà; Neugebauer, Martin; Bauer, Thomas; Ramunno, Lora; Vaccari, Alessandro; Berini, Pierre; Petrov, Yuriy; Danilov, Denis; Manshina, Alina; Banzer, Peter; Leuchs, Gerd (Small, 2019)
Carbon-based and carbon–metal hybrid materials hold great potential for applications in optics and electronics. Here, a novel material made of carbon and gold–silver nanoparticles is discussed, fabricated using a laser-induced self-assembly process. This self-assembled metamaterial manifests itself in the form of cuboids with lateral dimensions on the order of several micrometers and a height of tens to hundreds of nanometers. The carbon atoms are arranged following an orthorhombic unit cell, with alloy nanoparticles intercalated in the crystalline carbon matrix. The optical properties of this metamaterial are analyzed experimentally using a microscopic Müller matrix measurement approach and reveal a high linear birefringence across the visible spectral range. Theoretical modeling based on local-field theory applied to the carbon matrix links the birefringence to the orthorhombic unit cell, while finite-difference time-domain simulations of the metamaterial relates the observed optical response to the distribution of the alloy nanoparticles and the optical density of the carbon matrix.
CRIS-Team Scopus Importer:2019-05-02
Keywords: computational modeling; laser-induced deposition; metal alloy nanoparticles; microscopic Müller matrix measurement technique; orthorhombic carbon

Kelvin's chirality of optical beams - Nechayev, Sergey; Eismann, Jörg; Alaee, Rasoul; Karimi, Ebrahim; Boyd, Robert W.; Banzer, Peter (Physical Review A, 2021)
Geometrical chirality is a property of objects that describes a three-dimensional mirror-symmetry violation and therefore it requires a nonvanishing spatial extent. In contrary, optical chirality describes only the local handedness of electromagnetic fields and neglects the spatial geometrical structure of optical beams. In this Letter we put forward the physical significance of geometrical chirality of spatial structure of optical beams, which we term Kelvin's chirality. Furthermore, we report on an experiment revealing the coupling of Kelvin's chirality to optical chirality upon transmission of a focused beam through a planar medium. Our work emphasizes the importance of Kelvin's chirality in all light-matter interaction experiments involving structured light beams with spatially inhomogeneous phase and polarization distributions.
CRIS-Team Scopus Importer:2021-04-02

Large-Area 3D Plasmonic Crescents with Tunable Chirality - Görlitzer, Eric; Mohammadi, Reza; Nechayev, Sergey; Banzer, Peter; Vogel, Nicolas (Advanced Optical Materials, 2019)
Chiral plasmonic nanostructures hold promise for enhanced chiral sensing and circular dichroism spectroscopy of chiral molecules. It is therefore of interest to fabricate chiral plasmonic nanostructures with tailored chiroptical properties over large areas with reasonable effort. Here, a colloidal lithography approach is used to produce macroscopic arrays of sub-micrometer 3D chiral plasmonic crescent structures over areas >1 cm 2 . The chirality originates from symmetry breaking by the introduction of a step within the crescent structure. This step is produced by an intermediate layer of silicon dioxide onto which the metal crescent structure is deposited. It is experimentally demonstrated that the chiroptical properties in such structures can be tailored by changing the position of the step within the crescent. These experiments are complemented by finite element simulations and the application of a multipole expansion to elucidate the physical origin of the circular dichroism of the crescent structures.
CRIS-Team Scopus Importer:2019-06-04
Keywords: chirality; colloidal lithography; multipole decomposition; plasmonics; split-ring resonator

Lateral spin transport in paraxial beams of light - Neugebauer, Martin; Grosche, Simon; Rothau, Sergej; Leuchs, Gerd; Banzer, Peter (Optics Letters, 2016)
We investigate the lateral transport of (longitudinal) spin angular momentum in a special polarization tailored light beam composed of a superposition of a y-polarized zero-order and an x-polarized first-order Hermite-Gaussian mode. This phenomenon is linked to the relative Gouy phase shift between the individual modes upon propagation, but can also be interpreted as a geometric phase effect. Experimentally, we demonstrate the implementation of such a mode and measure the spin density upon propagation.

Lattice-plasmon-induced asymmetric transmission in two-dimensional chiral arrays - Apurv Chaitanya, N.; Butt, Muhammad; Reshef, O.; Boyd, Robert W.; Banzer, Peter; De Leon, Israel (APL Photonics, 2022)
Asymmetric transmission - direction-selective electromagnetic transmission between two ports - is a phenomenon exhibited by two-dimensional chiral systems. The possibility of exploiting this phenomenon in chiral metasurfaces opens exciting possibilities for applications such as optical isolation and routing without external magnetic fields. This work investigates optical asymmetric transmission in chiral plasmonic metasurfaces supporting lattice plasmon modes and unveils its physical origins. We show numerically and experimentally that asymmetric transmission is caused by an unbalanced excitation of such lattice modes by circularly polarized light of opposite handedness. The excitation efficiencies of the lattice modes, and hence, the strength of the asymmetric transmission, are controlled by engineering the in-plane scattering of the individual plasmonic nanoparticles such that the maximum scattering imbalance occurs along one of the in-plane diffraction orders of the metasurface. Furthermore, we show that only the nonzero diffraction orders contribute to this effect. By highlighting the role of the localized plasmon modes supported by the nanoparticle and their radiative coupling to the lattice structure, our study provides a guideline for designing metasurfaces with asymmetric transmission enabled by lattice plasmons.
CRIS-Team Scopus Importer:2022-02-04

Long distance free-space propagation of light carrying orbital angular momentum - Lavery, Martin P.J.; Peuntinger, Christian; Günthner, Kevin; Bauer, Thomas; Banzer, Peter; Elser, Dominique Alexander; Boyd, Robert W.; Padgett, Miles J.; Marquardt, Christoph; Leuchs, Gerd (Optics InfoBase Conference Papers, 2016)
We present analysis of the technical challenges facing deployment of longdistance free-space links employing orbital angular momentum multiplexing. Our analysis indicates atmospheric mitigation techniques, and modal purity are important consideration for system design.
CRIS-Team Scopus Importer:2022-06-05

Measuring the Kerr-nonlinearity of Ag in plasmonic nano-circuits - Kriesch, Arian; Pfeifer, Hannes; Burgos, Stanley P.; Ploss, Daniel; Banzer, Peter; Atwater, Harry A.; Peschel, Ulf (Nonlinear Optics 2013, 2013)
We observe nonlinear switching of ultrashort (600fs) laser pulses in subwavelength plasmonic nanocircuits. This allows us to experimentally determine the third-order nonlinear coefficient of silver.
EAM Import::2019-03-12

Microsphere kinematics from the polarization of tightly focused nonseparable light - Berg-Johansen, Stefan; Neugebauer, Martin; Aiello, Andrea; Leuchs, Gerd; Banzer, Peter; Marquardt, Christoph (Optics Express, 2021)
Recently, it was shown that vector beams can be utilized for fast kinematic sensing via measurements of their global polarization state [Optica 2, 864 (2015)]. The method relies on correlations between the spatial and polarization degrees of freedom of the illuminating field which result from its nonseparable mode structure. Here, we extend the method to the nonparaxial regime. We study experimentally and theoretically the far-field polarization state generated by the scattering of a dielectric microsphere in a tightly focused vector beam as a function of the particle position. Using polarization measurements only, we demonstrate position sensing of a Mie particle in three dimensions. Our work extends the concept of back focal plane interferometry and highlights the potential of polarization analysis in optical tweezers employing structured light.
CRIS-Team Scopus Importer:2021-04-30

Mimicking chiral light-matter interaction - Nechayev, Sergey; Banzer, Peter (Physical Review B, 2019)
We demonstrate that achiral electric-dipole scatterers can mimic an interaction of light with chiral matter by generating far-field circular polarization upon scattering, even though the optical chirality of the incident field as well as that of the scattered light is zero. On the one hand, the presented effect originates from the fact that electric-dipole scatterers respond selectively only to the incident electric field, which eventually results in depolarization of the transmitted beam and in generation of far-field circular polarization. On the other hand, although the incident beam does not possess any optical chirality, it lacks reflection symmetry and therefore it is geometrically chiral. To experimentally demonstrate this effect, we utilize a cylindrical vector beam with spiral polarization and a spherical gold nanoparticle positioned on the optical axis-the axis of rotational symmetry of the system. Our experiment and a simple theoretical model address the fundamentals of duality symmetry in optics and chiral light-matter interactions, accentuating their richness and ubiquity yet in highly symmetric configurations.
CRIS-Team WoS Importer:2019-06-25

Multi-twist polarization ribbon topologies in highly-confined optical fields - Bauer, Thomas; Banzer, Peter; Bouchard, Frederic; Orlov, Sergej; Marrucci, Lorenzo; Santamato, Enrico; Boyd, Robert W.; Karimi, Ebrahim; Leuchs, Gerd (New Journal of Physics, 2019)
Electromagnetic plane waves, solutions to Maxwell's equations, are said to be 'transverse' in vacuum. Namely, the waves' oscillatory electric and magnetic fields are confined within a plane transverse to the waves' propagation direction. Under tight-focusing conditions however, the field can exhibit longitudinal electric or magnetic components, transverse spin angular momentum, or non-trivial topologies such as Mobius strips. Here, we show that when a suitably spatially structured beam is tightly focused, a three-dimensional polarization topology in the form of a ribbon with two full twists appears in the focal volume. We study experimentally the stability and dynamics of the observed polarization ribbon by exploring its topological structure for various radii upon focusing and for different propagation planes.
CRIS-Team WoS Importer:2019-05-24

Nanoscale Vectorial Electric and Magnetic Field Measurement - Eismann, Jörg S.; Banzer, Peter (ACS Photonics, 2024)
In technology, old or new, from basic imaging through a camera lens to advanced applications such as fluorescence microscopy and optical lithography, there are countless examples that would be inconceivable without the utilization of focused light. As technology evolves, the demands on spatially confined light fields grow but so do the challenges of accurately characterizing these complex fields. This study introduces a technique to measure the full vectorial nature of light, reaching sub/wavelength spatial resolution while capturing the 3D amplitude and phase for both electric and magnetic fields. This is achieved based on a polarization-resolved far-field analysis of light scattered by a single spherical nanoparticle acting as a local probe. For experimental verification, the method is applied to tightly focused light fields under various input scenarios. Offering high resolution, precision, and flexibility, this technique shows great promise for both fundamental research and applications in technologies relying on highly localized light fields.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electromagnetic field metrology; nanoscale; scattering; tight focusing; vectorial fields

On the experimental investigation of the electric and magnetic response of a single nano-structure - Banzer, Peter; Peschel, Ulf; Quabis, Susanne; Leuchs, Gerd (Optics Express, 2010)
We demonstrate an experimental method to separately test the optical response of a single sub-wavelength nano-structure to tailored electric and magnetic field distributions in the optical domain. For this purpose a highly focused y-polarized TEM10-mode is used which exhibits spatially separated longitudinal magnetic and transverse electric field patterns. By displacing a single sub-wavelength nano-structure, namely a single split-ring resonator (SRR), in the focal plane, different coupling scenarios can be achieved. It is shown experimentally that the single split-ring resonator tested here responds dominantly as an electric dipole. A much smaller but yet statistically significant magnetic dipole contribution is also measured by investigating the interaction of a single SRR with a magnetic field component perpendicular to the SRR plane (which is equivalent to the curl of the electric field) as well as by analyzing the intensity and polarization distribution of the scattered light with high spatial resolution. The developed experimental setup as well as the measurement techniques presented in this paper are a versatile tool to investigate the optical properties of single sub-wavelength nano-structures.
EAM Import::2019-03-08

Orbital-to-spin angular momentum conversion employing local helicity - Nechayev, Sergey; Eismann, Jörg; Leuchs, Gerd; Banzer, Peter (Physical Review B, 2019)
Spin-orbit interactions in optics traditionally describe an influence of the polarization degree of freedom of light on its spatial properties. The most prominent example is the generation of a spin-dependent optical vortex upon focusing or scattering of a circularly polarized plane wave by a nanoparticle, converting spin to orbital angular momentum of light. Here we present a mechanism of conversion of orbital-to-spin angular momentum of light upon scattering of a linearly polarized vortex beam by a spherical silicon nanoparticle. We show that focused linearly polarized Laguerre-Gaussian beams of first order (l = +1) exhibit an -dependent spatial distribution of helicity density in the focal volume. By using a dipolar scatterer the helicity density can be manipulated locally, while influencing globally the spin and orbital angular momentum of the beam. Specifically, the scattered light can be purely circularly polarized with the handedness depending on the orbital angular momentum of the incident beam. We corroborate our findings with theoretical calculations and an experimental demonstration. Our work sheds light on the global and local properties of helicity conservation laws in electromagnetism.
CRIS-Team WoS Importer:2019-03-15

Resonant metamaterials for contrast enhancement in optical lithography - Dobmann, Sabine; Shyroki, Dzmitry; Banzer, Peter; Erdmann, Andreas; Peschel, Ulf (Optics Express, 2012)
The transmission through ultra-thin metal films is noticeable and thus limits their potential for the formation of lithographic masks. By sub-wavelength patterning of a metal film with a post structure, a resonant metamaterial is formed, which can effectively suppress the transmission. Measurements as well as calculations identify the width of the metal islands as a critical geometrical feature. Hence, the extraordinarily low transmission effect can be explained by the resonant response of single scatterers known as Localized Surface Plasmon Resonances (LSPR). A potential application of this suppressed transmission effect to thin metal masks in optical lithography is experimentally investigated.
EAM Import::2019-03-13

Shaping Field Gradients for Nanolocalization - Nechayev, Sergey; Eismann, Jörg; Neugebauer, Martin; Banzer, Peter (ACS Photonics, 2020)
Deep subwavelength localization and displacement sensing of optical nanoantennas have emerged as extensively pursued objectives in nanometrology, where focused beams serve as high-precision optical rulers while the scattered light provides an optical readout. Here, we show that in these schemes using an optical excitation as a position gauge implies that the sensitivity to displacements of a nanoantenna depends on the spatial gradients of the excitation field. Specifically, we explore one of such novel localization schemes based on the appearance of transversely spinning fields in strongly confined optical beams, resulting in far-field segmentation of left- and right-hand circular polarizations of the scattered light, an effect known as the giant spin-Hall effect of light. We construct vector beams with an augmented transverse spin density gradient in the focal plane and experimentally confirm enhanced sensitivity of the far-field spin segmentation to lateral displacements of an electric-dipole nanoantenna. We conclude that sculpturing of electromagnetic field gradients and intelligent design of scatterers pave the way toward further improvements in displacement sensitivity.
CRIS-Team Scopus Importer:2020-04-14
Keywords: displacement sensing; localization; nanoantennas; tight focusing; transverse spin

Spin-orbit coupling affecting the evolution of transverse spin - Eismann, Joerg S.; Banzer, Peter; Neugebauer, Martin (Physical Review Research, 2019)
We investigate the evolution of transverse spin in tightly focused circularly polarized beams of light, where spin-orbit coupling causes a local rotation of the polarization ellipses upon propagation through the focal volume. The effect can be explained as a relative Gouy-phase shift between the circularly polarized transverse field and the longitudinal field carrying orbital angular momentum. The corresponding rotation of the spatial distribution of the electric transverse spin density is observed experimentally by utilizing a recently developed reconstruction scheme, which relies on transverse-spin-dependent directional scattering of a nanoprobe.
CRIS-Team WoS Importer:2021-10-18

Spin-Orbit-Coupling Mediated by an Epsilon-Near-Zero Interface - Banzer, Peter; Eismann, Jörg; Ackermann, Lisa; Kantor, B.; Nechayev, S.; Alam, M. Z.; Fickler, R.; Boyd, R. W. (META 2023 Paris - France, 2023)
Taking advantage of a fundamental laws of geometrical optics, i.e., Fresnel equations, allows for coupling polarization and spatial phase degrees of freedom. We show that this conversion of spin to orbital angular momentum can be accomplished by a simple planar, homogeneous, and isotropic layer of an epsilon-near-zero material.
CRIS-Team Scopus Importer:2024-12-16

Substrate-Induced Chirality in an Individual Nanostructure - Nechayev, Sergey; Barczyk, Rene; Mick, Uwe; Banzer, Peter (ACS Photonics, 2019)
We experimentally investigate the chiral optical response of an individual nanostructure consisting of three equally sized spherical nanoparticles made of different materials and arranged in 90 degrees bent geometry. Placing the nanostructure on a substrate converts its morphology from achiral to chiral. Chirality leads to pronounced differential extinction (circular dichroism) and optical rotation (circular birefringence), which would be strictly forbidden in the absence of a substrate or heterogeneity. This first experimental observation of the substrate-induced break of symmetry in an individual heterogeneous nanostructure sheds new light on chiral light-matter interactions at substrate-nanostructure interfaces.
CRIS-Team WoS Importer:2019-09-13

The photonic wheel - demonstration of a state of light with purely transverse angular momentum - Banzer, Peter; Neugebauer, Martin; Aiello, Andrea; Marquardt, Christoph; Lindlein, Norbert; Bauer, Thomas; Leuchs, Gerd (Journal of the European Optical Society: Rapid Publications, 2013)

The polarization properties of a tilted polarizer - Korger, Jan; Kolb, Tobias; Banzer, Peter; Aiello, Andrea; Wittmann, Christoffer; Marquardt, Christoph; Leuchs, Gerd (Optics Express, 2013)
Polarizers are key components in optical science and technology. Thus, understanding the action of a polarizer beyond oversimplifying approximations is crucial. In this work, we study the interaction of a polarizing interface with an obliquely incident wave experimentally. To this end, a set of Mueller matrices is acquired employing a novel procedure robust against experimental imperfections. We connect our observation to a geometric model, useful to predict the effect of polarizers on complex light fields. © 2013 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05

Toward a Corrected Knife-Edge-Based Reconstruction of Tightly Focused Higher Order Beams - Orlov, Sergej; Huber, Christian; Marchenko, Pavel; Banzer, Peter; Leuchs, Gerd (Frontiers in Physics, 2020)
The knife-edge method is an established technique for profiling of even tightly focused light beams. However, the straightforward implementation of this method fails if the materials and geometry of the knife-edges are not chosen carefully or, in particular, if knife-edges are used that are made of pure materials. Artifacts are introduced in these cases in the shape and position of the reconstructed beam profile due to the interaction of the light beam under study with the knife. Hence, corrections to the standard knife-edge evaluation method are required. Here we investigate the knife-edge method for highly focused radially and azimuthally polarized beams and their linearly polarized constituents. We introduce relative shifts for those constituents and report on the consistency with the case of a linearly polarized fundamental Gaussian beam. An adapted knife-edge reconstruction technique is presented and proof-of-concept tests are shown, demonstrating the reconstruction of beam profiles.
CRIS-Team WoS Importer:2021-01-22

Toward High-Speed Nanoscopic Particle Tracking via Time-Resolved Detection of Directional Scattering - Beck, Paul; Neugebauer, Martin; Banzer, Peter (Laser & Photonics Reviews, 2020)
Owing to their immediate relevance for high precision position sensors, a variety of different sub-wavelength localization techniques has been developed in the past decades. However, many of these techniques suffer from low temporal resolution or require expensive detectors. Here, a method is presented that is based on the ultrafast detection of directionally scattered light with a quadrant photodetector operating at a large bandwidth, which exceeds the speed of most cameras. The directionality emerges due to the position dependent tailored excitation of a high-refractive index nanoparticle with a tightly focused vector beam. A spatial resolution of (Formula presented.) and a temporal resolution of (Formula presented.) is reached experimentally, which is not a fundamental but rather a technical limit. The detection scheme enables real-time particle tracking and sample stabilization in many optical setups sensitive to drifts and vibrations.
CRIS-Team Scopus Importer:2020-08-14
Keywords: directional scattering; tight focusing; ultrafast nanolocalization; vector beams

Towards fully integrated photonic displacement sensors - Bag, Ankan; Neugebauer, Martin; Mick, Uwe; Christiansen, Silke; Schulz, Sebastian A.; Banzer, Peter (Nature Communications, 2020)
The field of optical metrology with its high precision position, rotation and wavefront sensors represents the basis for lithography and high resolution microscopy. However, the on-chip integration—a task highly relevant for future nanotechnological devices—necessitates the reduction of the spatial footprint of sensing schemes by the deployment of novel concepts. A promising route towards this goal is predicated on the controllable directional emission of the fundamentally smallest emitters of light, i.e., dipoles, as an indicator. Here we realize an integrated displacement sensor based on the directional emission of Huygens dipoles excited in an individual dipolar antenna. The position of the antenna relative to the excitation field determines its directional coupling into a six-way crossing of photonic crystal waveguides. In our experimental study supported by theoretical calculations, we demonstrate the first prototype of an integrated displacement sensor with a standard deviation of the position accuracy below λ/300 at room temperature and ambient conditions.
CRIS-Team Scopus Importer:2020-06-16

Transverse spinning of unpolarized light - Eismann, Jörg; Nicholls, L. H.; Roth, D. J.; Alonso, M. A.; Banzer, Peter; Rodriguez-Fortuno, F. J.; Zayats, A.; Nori, Franco; Bliokh, K. Y. (Nature Photonics, 2020)
It is well known that the spin angular momentum of light, and therefore that of photons, is directly related to their circular polarization. Naturally, for totally unpolarized light, polarization is undefined and the spin vanishes. However, for non-paraxial light, the recently discovered transverse spin component, orthogonal to the main propagation direction, is largely independent of the polarization state of the wave. Here, we demonstrate, both theoretically and experimentally, that this transverse spin survives even in non-paraxial fields (for example, focused or evanescent) generated from totally unpolarized paraxial light. This counterintuitive phenomenon is closely related to the fundamental difference between the meanings of 'full depolarization' for two-dimensional (2D) paraxial and 3D non-paraxial fields. Our results open an avenue for studies of spin-related phenomena and optical manipulation using unpolarized light.
CRIS-Team WoS Importer:2021-01-15

Tuning the chirality of a dipole moment in an achiral particle with structured light - Eismann, Jörg; Neugebauer, Martin; Banzer, Peter (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
In the last decade, the attention drawn towards electric and magnetic dipole moments induced in optical nanoantennas significantly increased because of their numerous potential applications. For example, certain combinations of electric and magnetic dipoles allow for controlling the polarization state and propagation direction of light at the nanoscale [1,2]. The underlying effects rely on specific orientations and phase relations between the individual electric and magnetic dipole moments. In a recent work [3] we presented a new addition to the toolbox of experimental nanophotonics, the so-called σ-dipole, consisting of parallel electric and magnetic dipole moments phase shifted by ±π/2. The name originates from its well-defined near- and far-field helicity of ±1 [4]. Utilizing a combination of in-phase radially and azimuthally polarized beams, tightly focused onto a silicon nanoparticle, a well-defined and controllable superposition of both σ-dipoles can be realized.
CRIS-Team Scopus Importer:2019-11-15

Vectorial vortex generation and phase singularities upon Brewster reflection - Barczyk, Rend; Nechayev, Sergey; Butt, Muhammad Abdullah; Leuchs, Gerd; Banzer, Peter (Physical Review A, 2019)
We experimentally demonstrate the emergence of an azimuthally polarized vectorial vortex beam with a phase singularity upon Brewster reflection of focused circularly polarized light from a dielectric substrate. The effect originates from the polarizing properties of the Fresnel reflection coefficients described in Brewster's law. An astonishing consequence of this effect is that the reflected field's Cartesian components acquire local phase singularities at Brewster's angle. Our observations are crucial for polarization microscopy and open avenues for the generation of exotic states of light based on spin-to-orbit coupling, without the need for sophisticated optical elements.
CRIS-Team WoS Importer:2019-07-02
Keywords: Angular momentum of light; Classical optics; Geometrical & wave optics; Imaging & optical processing; Light propagation; transmission & absorption; Optical vortices; Optics & lasers; Polarization of light

Waveguide properties of single subwavelength holes demonstrated with radially and azimuthally polarized light - Banzer, Peter; Leuchs, Gerd; et al. (Applied Physics B-Lasers and Optics, 2007)
We investigate the transmission of focused beams through single subwavelength holes in a silver film. We use radially and azimuthally polarized light to excite higher-order waveguide modes as well as to match the radial symmetry of the aperture geometry. Remarkably, the transmission properties can be described by a classical waveguide model even for thicknesses of the silver film as thin as a quarter of a wavelength. © 2007 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2007.nat.dphy.optik.1optik.wavegu

Weak Measurement Enhanced Spin Hall Effect of Light for Particle Displacement Sensing - Neugebauer, Martin; Nechayev, Sergey; Vorndran, Martin; Leuchs, Gerd; Banzer, Peter (Nano Letters, 2019)
A spherical nanoparticle can scatter tightly focused optical beams in a spin-segmented manner, meaning that the far field of the scattered light exhibits laterally separated left- and right-handed circularly polarized components. This effect, commonly referred to as giant spin Hall effect of light, strongly depends on the position of the scatterer in the focal volume. Here, a scheme that utilizes an optical weak measurement in a cylindrical polarization basis is put forward to drastically enhance the spin-segmentation and, therefore, the sensitivity to small displacements of a scatterer. In particular, we experimentally achieve a change of the spin-splitting signal of 5% per nanometer displacement.
CRIS-Team Scopus Importer:2019-05-07
Keywords: localization; scattering; spin Hall effect; structured light; Weak measurement